Improving Transparency and Accountability in Public-Private Partnerships : Disclosure Diagnostic Report - Uganda - World Bank (World Bank, Washington, DC, 2020)
Between December 2017 and April 2018, a joint Government of Uganda and World Bank team conducted a study on public-private partnership (PPP) disclosure in Uganda, using the PPP Disclosure Diagnostic template recommended by the World Bank Framework for Disclosure of Information in PPPs. This study has been consolidated in the form of a PPP Disclosure Diagnostic Report (hereinafter Diagnostic Report) for Uganda. The Diagnostic Report examines the political, legal, and institutional environment for disclosure in PPPs. Based on a gap assessment exercise with key political, legal, institutional, and process findings benchmarked against the World Bank’s framework, the Diagnostic Report makes specific recommendations to improve disclosure, including recommended customized guidelines for PPP disclosure in Uganda. The findings suggest that there has been movement toward greater transparency and openness in all areas of government in Uganda, with several new initiatives having been launched in recent years. The 1995 Constitution of Uganda created new obligations on public bodies to promote more transparent governance structures. This was enhanced substantially with the enactment of the Access to Information Act 2005 (as well as the issuing of Access to Information Regulations in 2011), which, among other things, promotes proactive disclosure of information held by public authorities. Uganda has taken other progressive steps, such as signing the United Nations Convention Against Corruption and the African Union Convention on Preventing and Combating Corruption. In 2010, Uganda formulated its National e-Government Policy, which, among others, formed the basis for the establishment of the Ministry of ICT and National Guidance. The policy identifies several services and processes that are being progressively rolled out on Internet-based platforms for greater efficiency and transparency. These include government-to-government services, such as implementing financial management information systems; government-to-citizen, services, such as provision of passports and other certification services; and government-to-business services, such as e-procurement for government tenders.